Comparative study of allogenic and xenogeneic mesenchymal stem cells on cisplatin-induced acute kidney injury in Sprague-Dawley rats. Issue 1 (December 2016) - Ashour, Rehab; Saad, Mohamed-Ahdy; Sobh, Mohamed-Ahmed; Al-Husseiny, Fatma; Abouelkheir, Mohamed; Awad, Amal; Elghannam, Doaa; Abdel-Ghaffar, Hassan; Sobh, Mohamed
Abstract Background The paracrine and regenerative activities of mesenchymal stem cells (MSCs) may vary with different stem cell sources. The aim of the present study is to compare the effects of MSCs from different sources on acute kidney injury (AKI) induced by cisplatin and their influence on renal regeneration. Methods A single intraperitoneal injection of cisplatin (5 mg/kg) was used to induce AKI in 120 Sprague-Dawley rats. Rats were treated with either rat bone marrow stem cells (rBMSCs), human adipose tissue-derived stem cells (hADSCs), or human amniotic fluid-derived stem cells (hAFSCs). 5 × 106 MSCs of different sources were administered through rat tail vein in a single dose, 24 hours after cisplatin injection. Within each group, rats were sacrificed at the 4th, 7th, 11th, and 30th day after cisplatin injection. Serum creatinine, BUN, and renal tissue oxidative stress parameters were measured. Renal tissue was scored histopathologically for evidence of injury, regeneration, and chronicity. Immunohistochemistry was also done using Ki67 for renal proliferative activity evaluation. Results MSCs of the three sources were able to ameliorate cisplatin-induced renal function deterioration and tissue damage. The rat BMSCs-treated group had the lowest serum creatinine by day 30 (0.52 ± 0.06) compared to hADSCs and hAFSCs. All MSC-treated groups had nearly equal antioxidant activity as indicated by the decreased renal tissue malondialdehyde (MDA) and increased reduced glutathione (GSH) level and superoxide dismutase (SOD) activity at different time intervals. Additionally, all MSCs improved injury and regenerative scores. Rat BMSCs had the highest count and earliest proliferative activity in the renal cortex by day 7 as identified by Ki67; while, hAFSCs seem to have the greatest improvement in the regenerative and proliferative activities with a higher count of renal cortex Ki67-positive cells at day 11 and with the least necrotic lesions. Conclusions Rat BMSCs, hADSCs, and hAFSCs, in early single IV dose, had a renoprotective effect against cisplatin-induced AKI, and were able to reduce oxidative stress markers. Rat BMSCs had the earliest proliferative activity by day 7; however, hAFSCs seemed to have the greatest improvement in the regenerative activities. Human ADSCs were the least effective in the terms of proliferative and regenerative activities.